2019
DOI: 10.1111/ctr.13681
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐IL‐2R blockers comparing with polyclonal antibodies: Higher risk of rejection without negative mid‐term outcomes after ABO‐incompatible kidney transplantation

Abstract: There is no recommendation regarding the type of induction therapy to use in ABOincompatible (ABOi) kidney transplantation. The aim of this retrospective study was to compare the outcome of ABOi living donor kidney transplant (LDKT) recipients who received either polyclonal antibodies or anti-interleukin-2 receptor (IL-2R) blockers as an induction agent. All ABOi HLA-compatible patients that received a LDKT between 03/11 and 03/18 in three French transplantation center (Paris Saint-Louis, Paris Necker, and Tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is in contrast to the original Swedish protocol that propagated ABOi kidney transplantation reporting very low rejection rates [ 27 ], but the higher rejection rate in our ABOi compared with ABOc recipients is in line with later reports describing cellular rejection rates in up to one‐third of all ABOi kidney transplantation [ 28 , 29 ]. Higher rejection rates were also observed for rituximab/basiliximab versus rituximab/ATG in a single‐center ABOi induction comparison, however, with similar graft survival [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the original Swedish protocol that propagated ABOi kidney transplantation reporting very low rejection rates [ 27 ], but the higher rejection rate in our ABOi compared with ABOc recipients is in line with later reports describing cellular rejection rates in up to one‐third of all ABOi kidney transplantation [ 28 , 29 ]. Higher rejection rates were also observed for rituximab/basiliximab versus rituximab/ATG in a single‐center ABOi induction comparison, however, with similar graft survival [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For recipients with high immunological risk, ATG was suggested as the alternative. To further evaluate long‐term prognosis, Bello et al 47 conducted a retrospective study in three transplant centers in France. They found that the rabbit‐derived (rATG) group was similar to the anti IL‐2 group in terms of patient survival, graft survival rate, and infection complications 1 year after surgery, whereas the biopsy‐proved AMR rate was lower in the rATG group.…”
Section: Current Proceduresmentioning
confidence: 99%